2011
DOI: 10.1242/jcs.092791
|View full text |Cite
|
Sign up to set email alerts
|

MAL/MRTF-A controls migration of non-invasive cells by upregulation of cytoskeleton-associated proteins

Abstract: SummaryMonomeric actin regulates gene expression through serum response factor (SRF) by inhibiting its transcriptional coactivator myocardinrelated transcription factor (MAL/MRTF). Many affected genes encode cytoskeletal components. We have analysed the migratory effects of actin-MAL signalling and of new target genes in non-invasive highly adherent cells. Expression of active MAL impaired migration of both fibroblasts and epithelial cells, whereas dominant-negative constructs and partial knockdown of MAL/MRTF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 52 publications
2
60
0
Order By: Relevance
“…Furthermore, loss of CDH11 either in Cdh11 −/− mouse dermal fibroblasts or in shCDH11 human dermal fibroblasts abolished the expression of transcription factors known to affect ECM synthesis (Ueyama et al, 2003;Medjkane et al, 2009;Small et al, 2010;Leitner et al, 2011;Velasquez et al, 2013;Johnson et al, 2014;Parreno et al, 2014), such as MYOCD, MRTF-A, SRF and to a lesser extent MRTF-B. In agreement, knocking down either MYOCD or MRTF-A and -B decreased CDH11-mediated expression of collagen and elastin, but the effects of MRTF-A and -B were significantly stronger.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, loss of CDH11 either in Cdh11 −/− mouse dermal fibroblasts or in shCDH11 human dermal fibroblasts abolished the expression of transcription factors known to affect ECM synthesis (Ueyama et al, 2003;Medjkane et al, 2009;Small et al, 2010;Leitner et al, 2011;Velasquez et al, 2013;Johnson et al, 2014;Parreno et al, 2014), such as MYOCD, MRTF-A, SRF and to a lesser extent MRTF-B. In agreement, knocking down either MYOCD or MRTF-A and -B decreased CDH11-mediated expression of collagen and elastin, but the effects of MRTF-A and -B were significantly stronger.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, loss of MRTF-A reduced the levels of DSG1 messenger RNA (mRNA) in keratinocytes, suggesting that DSG1 is directly regulated by the SRF/MRTF-A complex . Another experiment showed that MRTF-A and SRF were recruited to cis-regulatory elements of the PKP2 gene to regulate its expression (Leitner et al 2011). Taken together, these data suggest that RhoA/MRTF-A signaling in keratinocytes affects the expression of desmosomal proteins directly and indirectly although the regulation via SRF/MRTF-A in response to mechanical strain has not been directly shown.…”
Section: Mechanosensitive Signaling Pathways In the Control Of Desmosmentioning
confidence: 93%
“…1a-d) that MRFT-A induced hallmarks of angiogenesisthat is, migration and tube formation of cultured human microvascular endothelial cells-to a similar extent as T 4. The pro-angiogenic effect of MRTF-A was dependent on the G-acting-binding motif of T 4, as mutating this domain and annihilating G-acting binding abolished the T 4 effect on vessel growth, as did a short-hairpin RNA (shRNA) interfering simultaneously with MRTF-A and B transcription (MRTF-shRNA) 27 . Consistently, T 4 enhanced nuclear MRTF-A translocation (Fig.…”
Section: T 4 and Mrtf-mentioning
confidence: 99%